Pengaruh Likuiditas, Struktur Aset, Profitabilitas dan Free Cashl Flowl terhadap Kebijakan Hutang - Dhistianti Mei Rahmawantari (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to examine the effect of Liquidity, Asset Structure, Profitability and Free Cash Flow on Debt Policy in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX for the 2018-2022 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 155 data. The results showed that liquidity had no effect on debt policy, asset structure had no effect on debt policy, profitability had a significant effect on debt policy, and free cash flow had a significant negative effect on debt policy